Patterns of Abuse among Older Adults in General Outpatients Clinic of UATH Abuja, Nigeria. - Nanna R. Ripiye; Tunde M. Ojo; Chika Q. Onwundinjo; Victor Ameh; Nicholas D. Baamlong (Nigerian Frontline Medicine Journal)
Background: Elder abuse refers to any intentional act or neglect that causes harm or distress to an older adult. It affects a significant number of older adults globally and can occur in homes, nursing homes, or assisted living facilities. Abuse can be financial, physical, emotional, or even take the form of neglect. The consequences of elder abuse are usually devastating and may affect the individual's quality of life. This study sets out to assess the abuse among older adults a ending the General Outpatient Clinic and its relationship to social support.